Courtney Kerrigan. Summary and reflections on the book "Death and Life of the Great American School System" by Diane Ravitch : Courtney Kerrigan. Summary and reflections on the book "Death and Life of the Great American School System" by Diane Ravitch - Kerrigan, Courtney A. (Young Scholars Grinchenko – Seton International Journal, 2022)
Courtney Kerrigan. Summary and reflections on the book "Death and Life of the Great American School System" by Diane Ravitch